A fountain filled with blood [large type] - Spencer-Fleming, Julia (Spencer-Fleming, Julia. Clare Fergusson/Russ Van Alstyne mystery., 2014)
It's the Fourth of July, and a violent attack on the town's medical examiner triggers a series of assaults on other gay men in Millers Kill, New York. Episcopal priest Clare Fergusson wants to call them out as hate crimes. Police Chief Russ Van Alstyne wants to keep his investigation quiet. When a controversial resort developer is found brutally murdered, Clare and Russ must put aside their sharp differences -- and their keen attraction -- to connect the crimes. As the temperature rises, a killer sets a deadly trap in the mountains.